Problems of differential diagnostics between tuberculosis of lungs and nonspecific pneumonia - Yasinskyi, R. M.; Varahabhatla, V.; Tekwani, V. (Запорізький державний медичний університет, 2018)
Introduction. The frequency of variation between the primary and the specified diagnoses in the differential diagnosis of nonspecific pneumonia (P) and tuberculosis (TB) is 30-40%, and the timing of the diagnosis sometimes exceeds 1-3 months. Aim. To demonstrate the difficulty in differentiation between TB and P in cases of lung lesions. Materials and methods. We analyzed 10 cases of variation between the primary and the specified diagnoses in the differential diagnosis of P and TB, hospitalized in Zaporizhzhia regional antituberculosis dispensary during last 3 years (2014-2017).
Keywords: тези доповідей